2007
DOI: 10.1007/s00216-007-1211-5
|View full text |Cite
|
Sign up to set email alerts
|

A novel microbial biosensor based on cells of Gluconobacter oxydans for the selective determination of 1,3-propanediol in the presence of glycerol and its application to bioprocess monitoring

Abstract: Novel and selective microbial amperometric biosensors that use Gluconobacter oxydans cells to monitor the bacterial bioconversion of glycerol (Gly) to 1,3-propanediol (1,3-PD) are described. Two different mediators, ferricyanide and flexible polyvinylimidazole osmium functionalized polymer (Os-polymer), were employed to prepare two different microbial biosensors, both of which gave high detection performance. The good operational stabilities of both types of biosensor were underlined by the ability to detect 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(24 citation statements)
references
References 28 publications
0
23
1
Order By: Relevance
“…4.1 1,3-propanediol 1,3-propanediol is a typical and the oldest product of glycerol fermentation (Katrlík et al, 2007) Guo et al (2009) reported that Klebsiella pneumoniae CPSdeficient mutant (unable to produce capsular polysaccharides) in fed-batch fermentation was able to synthesize 78.13 g/L of 1,3-propanediol with yield and productivity of 0.53 mol/mol of glycerol and 1.95 g/L/h, respectively. Tang et al (2009) studied bioconversion of glycerol to 1,3-propanediol using engineered strain of Escherichia coli.…”
Section: Crude Glycerol Utilization In Biotechnologymentioning
confidence: 99%
“…4.1 1,3-propanediol 1,3-propanediol is a typical and the oldest product of glycerol fermentation (Katrlík et al, 2007) Guo et al (2009) reported that Klebsiella pneumoniae CPSdeficient mutant (unable to produce capsular polysaccharides) in fed-batch fermentation was able to synthesize 78.13 g/L of 1,3-propanediol with yield and productivity of 0.53 mol/mol of glycerol and 1.95 g/L/h, respectively. Tang et al (2009) studied bioconversion of glycerol to 1,3-propanediol using engineered strain of Escherichia coli.…”
Section: Crude Glycerol Utilization In Biotechnologymentioning
confidence: 99%
“…Thus, the thermally expanded graphite is a material with good electrical conductivity, high specific surface area up to 2000 m 2 /g, biocompatibility, chemical resistance in corrosive environments and can be a long time in the technical operation [37]. These qualities allow immobilization on the electrode TRG surface of the high superficial concentration of bacterial or their membrane fractions.…”
Section: Development Of the Bioanode Of A Fuel Element On The Basis Omentioning
confidence: 99%
“…It is also used as a monomer for the production of biodegradable polymers (polyesters, polyether, polyurethanes, etc. ), cosmetics, lubricants, medicines, and as an intermediate for the synthesis of heterocyclic compounds (Regan and Crawford, 1994;Menzel et al, 1997;Katrlík et al, 2007;Biebl et al, 1999;. Recently, 1,3-PD has also been used as a monomer to synthesize a new type of polyester -polytrimethylene terephthalate (Biebl et al, 1999;Zeng and Biebl, 2002;Liu et al, 2007;Zhang et al, 2007).…”
Section: Author(s) Agree That This Article Remain Permanently Open Acmentioning
confidence: 99%